Man, economy and state vol.1 - Rothbard, Murray N. (Princeton, 1962)
One of the unhappy casualties of World War I, it seems, was the old-fashioned treatise on economic "principles." Before World War I, the standard method, both of presenting and advancing economic thought, was to write a disquisition setting forth one's vision of the corpus of economic science. A work of this kind had many virtues wholly missing from the modern world. On the one hand, the intelligent layman, with little or no previous acquaint ance with economics, could read it. On the other hand, the author did not limit himself, textbook-fashion, to choppy and oversimpli fied compilations of currently fashionable doctrine. For better or worse, he carved out of economic theory an architectonic-an edifice. Sometimes the edifice was an original and noble one, sometimes it was faulty; but at least there was an edifice, for be ginners to see, for colleagues to adopt or criticize. Hyperrefine ments of detail were generally omitted as impediments to viewing economic science as a whole, and they were consigned to the journals. The university student, too, learned his economics from the treatise on its "principles"; it was not assumed that special works were needed with chapter lengths fitting course require ments and devoid of original doctrine. These works, then, were read by students, intelligent laymen, and leading economists, all of whom profited from them.
Keywords: Economics